Impact of chilled ceiling in a high sensible cooling load room with underfloor air distribution. (3rd July 2019) - Wu, Xiaozhou; Gao, Jie; Wang, Haichao; Wang, Fenghao; Tian, Zhen
Abstract : The use of an underfloor air distribution (UFAD) system integrated with a chilled ceiling (CC) cooling system can provide a potentially advanced heating, ventilation, and air conditioning (HVAC) system with high sensible cooling loads in modern office buildings. In this paper, an experimental study of the impact of CC in a room with a high sensible cooling load with UFAD was performed when the chilled ceiling surface temperature increased from 17.0 to 26.0 °C. The vertical distributions of indoor air temperature, air velocity, and pollutant (CO2 ) concentration were measured and evaluated by the vertical air temperature difference (VATD), turbulence intensity (TI), and contaminant removal effectiveness (CRE), respectively. The results showed that the average VATD, TI, and CRE were 0.1–0.9 °C, 4–40%, and 0.85–1.19, respectively, when the internal and external sensible cooling loads equal 41.5W/m 2 . These evaluation indices varied clearly when the internal sensible cooling load increased from 41.5 to 69.5W/m 2, whereas they were almost the same when the external sensible cooling load increased from 41.5 to 69.5W/m 2 . The minimum CRE and air diffusion performance index (ADPI) coincided with the maximum heat removal effectiveness (HRE) under a constant cooling load condition. The results suggest that it is better to balance the energy consumption as well as indoor air quality and thermal comfort in a room with UFAD + CC.